Industrial Relations An Islamic Approach - Hoque, Nazamul (IIUC Studies, 2014)
Industrial relations (IR) have been found to have a significant impact on the organizational performance. Good industrial relation is the outcome of integrated and just efforts of employer, managers, workers, and state. Since Islam is a complete code of life, all Muslims must abide by the rules and regulations of Islam in developing and maintaining industrial relations. But lack of adequate Islamic guidelines regarding IR is one of the very important constraints to the way of practicing it from Islamic point of view in the Muslim world. So this study is an attempt to minimize the gap found therein. In this study some fundamental principles of Islamic IR are developed along with the specific roles of employers, managers, workers, and state from Islamic perspectives. If all parties perform their roles as per the guidelines of this study it is expected that each and every party would be benefited highly through developing good IR both here and here after. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20402 IIUC Studies Vol.8 December 2011: 39-58